(untitled) (Bangladesh Journal of Child Health, 2013)
Nephrogenic Diabetes Insipidus (NDI) may occur as a complication of chronic kidney disease (CKD). The incidence of NDI is very rare. So recognition of this potential complication is very important. In our country, this rare complication is not yet reported. So, to make awareness among the paediatricians, we report a case of NDI as a rare complication of CKD. A 4-year old boy was admitted in the Department of Paediatric Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU) with the complaints of failure to thrive, refusal to feed, nausea and vomiting since 18- months of his age. For the last six months, he had also complaints of polyuria and polydipsia. In addition to this, he developed muscle pain, constipation, bowing of leg and occasional unexplained fever. He was moderately pale with deep sighing respiration and his blood pressure was above 95th centile for age and sex. His creatinine level was high with low TCO2 and calcium level. His plasma osmolality was very high while urine osmolality was inappropriately low which did not increase after desmopressin (nasal spray) administration. Initial treatment with Indomethacin was ineffective while the combination of hydrochlorothiazide and Indomethacin was effective and well tolerated. DOI: http://dx.doi.org/10.3329/bjch.v37i1.15350 BANGLADESH J CHILD HEALTH 2013; VOL 37 (1) : 41-44